Go Spy Out the Land: Intelligence Preparations for World War I in South West Africa - Stejskal, James (Scientia Militaria - South African Journal of Military Studies, 2016)
As World War I approached, the potential for conflict drove the principal future protagonists, England and Germany, to seek detailed information on their anticipated enemies, not just in Europe, but wherever their nations’ interests crossed paths. After 1910, the Union of South Africa turned its eyes to the northwest to keep watch on its German neighbour in the colonial protectorate of Deutsch-Südwest-afrika. For South Africans of English descent, the question of Germany’s intentions was especially important: the Kaiser’s vow of support for the Afrikaners prior to the recently concluded Boer War of Independence (South African War) was still remembered with some trepidation, despite its bombastic nature.[i] Despite this, neither side was prepared for war outside Europe. The study on which this article reports, investigated the role intelligence played in the African theatre of the conflict, specifically the South West African campaign, and how this affected the preparation, conduct, and final outcome of the war for both the Allies and the Germans. While few records of the missions undertaken or the intelligence produced survive to describe intelligence operations in detail, enough exists to paint a picture of the efforts undertaken during the war. The activities of English defence attachés, German Schutztruppe officers on leave, South African Scouts, as well as alleged spies were examined and we demonstrate here that military intelligence operations – where successfully undertaken – provided policy makers and military leaders alike with the information necessary for the prosecution of the war.